Emerenciana Maria de Jesus, cabra, free person, single:trajectory of a matrifocal Family in the Parish of Seridó (eighteenth-nineteenth centuries) - Macedo, Helder Alexandre Medeiros de (Temporalidades, 2025)
The history of slavery and miscegenation in the Seridó of Rio Grande do Norte has advanced considerably, with works that seek to understand these phenomena as connected and which resulted, to a large extent, in the formation of part of the sertanejo families. From the analysis of sources from the Parish of Seridó and judicial sources of the District of Caicó, made with the help of the Micro-History methodology, the work seeks to investigate a life trajectory, that of Emerenciana Maria de Jesus, a cabra woman (“cabra” is a local term that was used to designate slave and then free people. At the time of the study, it was used to adjectivate non-white people, and mestizos) free person and single. The examination of the trajectory of this matrifocal family allows us to shed light on the naming of mestizo people in the Seridó, with the quality of "cabra", and the loss of this qualifier over the generations, being replaced by that of pardo or P.